2011
DOI: 10.1074/jbc.m111.258897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Src Kinase Phosphorylation on Disordered C-terminal Domain of N-Methyl-d-aspartic Acid (NMDA) Receptor Subunit GluN2B Protein

Abstract: NMDA receptors are ligand-gated ion channels with a regulatory intracellular C-terminal domain (CTD). In GluN2B, the CTD is the largest domain in the protein but is intrinsically disordered. The GluN2B subunit is the major tyrosine-phosphorylated protein in synapses. Src kinase phosphorylates the GluN2B CTD, but it is unknown how this affects channel activity. In disordered proteins, phosphorylation can tip the balance between order and disorder. Transitions can occur in both directions, so it is not currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Tyrosine phosphorylation of CTD2 by Src kinase is known to alleviate Zn 2ϩ inhibition, but nothing is known about how the CTD modulates gating. We showed that Src phosphorylation increased R H , indicating polypeptide expansion (19). Thus, we reasoned that alterations in the underlying dynamics of this disordered region were involved in allosteric regulation of GluN2B-containing receptors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tyrosine phosphorylation of CTD2 by Src kinase is known to alleviate Zn 2ϩ inhibition, but nothing is known about how the CTD modulates gating. We showed that Src phosphorylation increased R H , indicating polypeptide expansion (19). Thus, we reasoned that alterations in the underlying dynamics of this disordered region were involved in allosteric regulation of GluN2B-containing receptors.…”
Section: Discussionmentioning
confidence: 99%
“…6D). Unlike wild type CTD2 (19), the higher FRET state was still predominant even after phosphorylation. Proline depletion does not prevent the polypeptide expansion induced by Src phosphorylation.…”
Section: Prediction Of Disorder In the Glun2bmentioning
confidence: 97%
See 3 more Smart Citations